Revenge and the “New” Americans - Yiorgos Kalogeras (Ex-centric Narratives: Journal of Anglophone Literature, Culture and Media, 2017)
A persistent theme in American ethnic fiction and film involves an ethnic or immigrant character who dreams of and/or performs an act of violence which goes against the law of the land; on the contrary, it is prescribed by a pre-American law, or unwritten custom. Application of such a pre-American law though engenders a question: why should a new American citizen resort to the dictates of a pre-industrial past rather than to the laws of a modern, well-organized, bureaucratic society? This paper claims that, paradoxically, these acts inspired by a pre-American set of beliefs and attitudes expedite the transition of the immigrant and ethnic into the mainstream and post-ethnicity. Contextualized as part of organized crime, labor politics, predatory capitalism, the myth of the Golden Door these violent acts configure as ethnic but are motivated by the desire of the protagonist to join America and move on to a post-ethnic identity. The author analyzes Anzia Yezierska’s “The Lost Beautifulness” (1920), Harry Mark Petrakis’s “Pericles on 31st Street” (1957), and George Pelecanos’s “The Dead, Their Eyes Implore Us” (2003).